L’indirection comme procédé de persuasion en publicité - Gilles Gauthier (Communication, 2000)
The oblique nature of the persuasion of advertising is examined in relation to nondirectionality: the possibility of producing a primary act of discourse by the accomplishment of a secondary act of discourse. Taking into consideration the typology of acts of discourse and their conditions of accomplishment allows for the identification of a certain number of methods by which nondirectionality functions. The study of a body of advertisements in Québécois women’s magazines leads to the identification of five specific methods of nondirectionality. The two most commonly employed are: (1) persuading the reader to use a product by claiming that the product will be beneficial (or that it will meet a need or expectation of the reader) and (2) pledging a result by affirming that it will be obtained.